Immunological identity of brucella native hapten, polysaccharide B, and yersinia enterocolitica serotype 9 native hapten. - Fernandez-Lago, L (1982)
Yersinia enterocolitica serotype 9 contained an antigenic component giving a reaction of total identity with Brucella native hapten and polysaccharide B. This component was present in a phenol-water extract (fraction 5; M. Redfearn, Ph.D. Thesis, University of Wisconsin, Madison, 1960) along with the smooth lipopolysaccharide. The native hapten could be purified free of lipopolysaccharide and proteins by gel filtration.